Status Hukum Anak Akibat Perkawinan Batal dalam Perspektif Hak Asasi Manusia dan Perlindungan Anak - Safarika Khumayiroh; Efa Rodiah Nur; Liky Faizal; Maimun Maimun; Dian Eka Putri (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This study examines the legal status of children resulting from an annulled marriage from the perspective of human rights and child protection. This study aims to analyze the legal status of children resulting from an annulled marriage from the perspective of human rights and child protection. In judicial practice, annulment decisions often omit the status of children born from the marriage. Judges generally focus solely on the validity of the marriage, rather than on fulfilling the rights of children born from the relationship. This situation creates a legal gap because, even though the child is not at fault for the annulment of their parents' marriage, their legal status is often unclear, impacting the protection of their rights. The purpose of this study is to examine the extent to which human rights and child protection principles are integrated into judges' legal considerations when deciding annulment cases. This research uses a normative legal method with a statutory approach and case studies of several relevant court decisions. The research results show that the omission of the child's status in the verdict has the potential to conflict with the principles of non-discrimination and the best interests of the child as stipulated in the Convention on the Rights of the Child (CRC), which Indonesia has ratified through Presidential Decree No. 36 of 1990, and Law No. 35 of 2014 concerning Child Protection. From a human rights perspective, children born from an annulled marriage still have a civil relationship with their mother and their mother's family as stipulated in Article 43 paragraph (1) of the Marriage Law and the Constitutional Court Decision, No. 46/PUU-VII/2010.